Maternal but not fetoplacental health can be improved by metformin in a murine diet‐induced model of maternal obesity and glucose intolerance. (29th September 2021) - Hufnagel, Antonia; Fernandez‐Twinn, Denise S.; Blackmore, Heather L.; Ashmore, Thomas J.; Heaton, Robert A.; Jenkins, Benjamin; Koulman, Albert; Hargreaves, Iain P.; Aiken, Catherine E.; Ozanne, Susan E.
Abstract : Abstract: Maternal obesity is a global problem that increases the risk of short‐ and long‐term adverse outcomes for mother and child, many of which are linked to gestational diabetes mellitus. Effective treatments are essential to prevent the transmission of poor metabolic health from mother to child. Metformin is an effective glucose lowering drug commonly used to treat gestational diabetes mellitus; however, its wider effects on maternal and fetal health are poorly explored. In this study we used a mouse (C57Bl6/J) model of diet‐induced (high sugar/high fat) maternal obesity to explore the impact of metformin on maternal and feto‐placental health. Metformin (300 mg kg −1 day −1 ) was given to obese females via the diet and was shown to achieve clinically relevant concentrations in maternal serum (1669 ± 568 nM in late pregnancy). Obese dams developed glucose intolerance during pregnancy and had reduced uterine artery compliance. Metformin treatment of obese dams improved maternal glucose tolerance, reduced maternal fat mass and restored uterine artery function. Placental efficiency was reduced in obese dams, with increased calcification and reduced labyrinthine area. Consequently, fetuses from obese dams weighed less ( P < 0.001) at the end of gestation. Despite normalisation of maternal parameters, metformin did not correct placental structure or fetal growth restriction. Metformin levels were substantial in the placenta and fetal circulation (109.7 ± 125.4 nmol g −1 in the placenta and 2063 ± 2327 nM in fetal plasma). These findings reveal the distinct effects of metformin administration during pregnancy on mother and fetus and highlight the complex balance of risk vs . benefits that are weighed in obstetric medical treatments. Key points: Maternal obesity and gestational diabetes mellitus have detrimental short‐ and long‐term effects for mother and child. Metformin is commonly used to treat gestational diabetes mellitus in many populations worldwide but the effects on fetus and placenta are unknown. In a mouse model of diet‐induced obesity and glucose intolerance in pregnancy we show reduced uterine artery compliance, placental structural changes and reduced fetal growth. Metformin treatment improved maternal metabolic health and uterine artery compliance but did not rescue obesity‐induced changes in the fetus or placenta. Metformin crossed the placenta into the fetal circulation and entered fetal tissue. Metformin has beneficial effects on maternal health beyond glycaemic control. However, despite improvements in maternal physiology, metformin did not prevent fetal growth restriction or placental ageing. The high uptake of metformin into the placental and fetal circulation highlights the potential for direct immediate effects of metformin on the fetus with possible long‐term consequences postnatally. Abstract : Abstract figure legend Obesogenic diet during pregnancy leads to impaired metabolic health in the mother and reduced fetal growth and placental pathologies. Maternal metabolic health can be markedly improved by metformin treatment; however, this is not the case for fetal and placental health and metformin reaches the placenta and fetal circulation, which could have direct short‐ and long‐term effects.